Gerakan Da'wah Ishlah Imam Al-Ghazali Dan Pengaruhnya Dalam Sejarah Lahirnya Gerakan Shalahuddin Al-Ayyubi - Zamzamy, Muawwin Bihac; Manurung, Nirwan Syafrin; Irfani, Fahmi (Komunika: Journal of Communication Science and Islamic Dakwah, 2018)
Islam is religion (improvement). Al-Qur'an was revealed to reveal the conditions of human life, which ishas become the principle of the human perspective to address the dynamics of life. Therefore the movement of da'wah ish is something that is inherent (inseparable) from Islam itself. Imam Al-Ghazali is a well-known figure in the history of Muslims who not a few of the scholars consider him a mujaddid and mushlih (the perpetrator ishlah). In this study wanted to know what is Islam in Islam and how the movement of da'wah ishlah according to Imam Al- Ghazali and the steps and procedures are done by him to change the condition of Muslim society at that time. As for after that, it can only be known the influence of the movement of da'wah ish Imam Al-Ghazali in the history of the birth of the generation of Saladin Al-Ayyubi. This research is a library research study. And from the results of the research it appears that the movement of Da'wah ish Imam Al-Ghazali has two influences, the main influence of which is the emergence of madrassas that are the example of Al-Ghazali's education curriculum and system and the creation of cooperation and coordination between the teachers of all madrassas. General influence, the birth of the ummah al-mahjar (a solid community that embraces all the potential of the ummah), namely the Zanki Sultanate and also the Al-Ayyubi Sultanate and the realization of a complementary Islamic community in education, politics and the military, from this field Al-Ghazali ishlah influential in the history of the birth of the generation of Saladin Al-Ayyubi.